16 Relationship of mitral annular plane systolic excursion and intra-myocardial haemorrhage in reperfused st-elevation myocardial infarction. (26th April 2015) - Garg, P; Kidambi, A; Ripley, DP; Dobson, LE; Swoboda, PP; Musa, TA; McDiarmid, AK; Erhayiem, B; Greenwood, JP; Plein, S
Abstract : Background: Mitral annular plane systolic excursion (MAPSE) is known to have prognostic importance in patients with acute myocardial infarction (MI). In post-MI patients with MAPSE <8 mm, the combined mortality and hospitalisation incidence is 43.8%. Similarly, intra-myocardial haemorrhage (IMH) in the infarct-core is an independent marker of prognosis. We hypothesised that the MAPSE on 4-chamber cine-CMR is correlated to left ventricular ejection fraction (EF) and to the presence of IMH. Methods: Fourty-four patients received CMR examination at 3T (Achieva CV, Philips Healthcare, Best, The Netherlands) within 3 days following acute MI. Cine, T2-weighted, T2*-imaging and late gadolinium enhancement (LGE) imaging were performed. Infarct and microvascular obstruction (MO) extent were measured from LGE images. The presence and extent of IMH was investigated by combined analysis of T2w and T2* sequences. MAPSE was computed (medial, lateral and average) using the 4-chamber cine (Figure 1 ). Results: Mean age of our studied population was 58.27 ± 11.41. CMR parameters were as follows: LVEF 48.2 ± 11.4%; infarct volume of 15.5 ± 12.2 ml and averaged MAPSE of 10.27 ± 2.1 mm. Controlling for risk factors, IMH was strongly negatively correlated to average MAPSE (r=-0.65; p < 0.001). Averaged MAPSE was also moderately correlated to LVEF (r = 0.47; p = 0.001). Conclusion: Averaged MAPSE, which is a simple CMR derived parameter of longitudinal function, has the potential to predict the presence of IMH in the setting of re-perfused acute MI. This parameter could be easily measured at bedside by transthoracic echocardiography to predict presence of IMH. Funding: JPG and SP receive a research grant from Philips Healthcare. SP is funded by British Heart Foundation fellowship (FS/10/62/28409).